(untitled) (ModaPalavra e-periódico, 2016)
While performing physical activities, the effort made by the human body is releasing sweat and causes fatigue factors combined with others directly affect performance. Science and technology in the service ofsociety have developed and introduced products for the sports area with the most varied characteristics and properties derived from the transdisciplinary between the various areas of knowledge to maximizing the performance of athletes. The clothing is particularly important in this area where factors such as weight, heat transfer / moisture and structure can change your performance. In this perspective the main objective of this paper is presents results of the sportswear total design optimization providing for their application to the development of a multifunctional T-shirt for professional football players. Experiments have identified structures and properties that can be applied in certain contact zones T-shirt with the athlete’s body.